REQUIREMENTS FOR THE ESTABLISHMENT OF THE DEPARTMENT OF ARCHAEOLOGY OF CENTRAL ASIA - Mirzayev K. M. (TARIXIY TADQIQOTLAR, 2025)
This scientific article is devoted to the analysis of the history of the formation and development of archaeological science in Central Asia, as well as an assessment of its current state. Particular attention is given to the need for establishing a Department of Central Asian Archaeology and its significance for scientific research. It is noted that, considering the region’s rich historical and cultural heritage and its prominent role in the global archaeological community, the creation of such a department is of not only scientific but also cultural and educational importance. The article outlines possible directions for the development of research and educational programs that could be implemented within the framework of this new department.